How Do Sponsors Think about "Month 13"? - Lenard, Patti Tamara (Refuge, 2019)
There are many different ways in which one might describe the goal of Canada’s Private Sponsorship of Refugees Program. For sponsors, though, one goal is clear: to get “their” refugees ready to handle the rigors of “month 13.” The supposed ideal is that, by month 13, newcomers are employed and living independently in Canada, as productive members of society. The reality is messier. The objective in this article is to offer an account of how sponsors think of their job, in relation to month 13. Using data collected via interviews with nearly sixty private sponsors in Ottawa, it is shown that sponsors are motivated by securing stability for newcomers by the time month 13 arrives, but that sponsors differently flesh out the meaning of the stability they are seeking to achieve on behalf of newcomers. In particular, the data suggest, sponsors believe that newcomers’ attitude to integration is especially strongly related to their actual integration, and newcomers do especially well by month 13 to the extent that sponsors are able to build and support a positive attitude towards it.